Selection of Wine Saccharomyces cerevisiae Strains and Their Screening for the Adsorption Activity of Pigments, Phenolics and Ochratoxin A - Andrea Pulvirenti; Luciana De Vero; Giuseppe Blaiotta; Rossana Sidari; Giovanna Iosca; Maria Gullo; Andrea Caridi (Fermentation, 2020)
Ochratoxin A is a dangerous mycotoxin present in wines and is considered the principal safety hazard in the winemaking process. Several authors have investigated the ochratoxin A adsorption ability of Saccharomyces cerevisiae yeasts, and specifically selected strains for this desired trait. In the present work, a huge selection of wine yeasts was done starting from Portuguese, Spanish and Italian fermenting musts of different cultivars. Firstly, 150 isolates were collected, and 99 non-redundant S. cerevisiae strains were identified. Then, the strains were screened following a multi-step approach in order to select those having primary oenological traits, mainly (a) good fermentation performance, (b) low production of H2S and (c) low production of acetic acid. The preselected strains were further investigated for their adsorption activity of pigments, phenolic compounds and ochratoxin A. Finally, 10 strains showed the desired features. The goal of this work was to select the strains capable of absorbing ochratoxin A but not pigments and phenolic compounds in order to improve and valorise both the quality and safety of red wines. The selected strains are considered good candidates for wine starters, moreover, they can be exploited to obtain a further enhancement of the specific adsorption/non-adsorption activity by applying a yeast breeding approach.